2018
DOI: 10.1002/rcm.8071
|View full text |Cite
|
Sign up to set email alerts
|

Potential use of stable isotope and fatty acid analyses for traceability of geographic origins of jumbo squid (Dosidicus gigas)

Abstract: Combined use of stable isotope ratios and fatty acid analyses could trace geographic origins of jumbo squid. This study provides an alternative approach for improving authenticity evaluation of commercial squid products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Powdered muscle tissues were prepared and analyzed for FA profiles followed by the procedure outlined by our previous research (Gong et al, 2018a). Briefly, lipid samples were extracted from approximately 200 mg of dried powders using a mixture of chloroform and methanol.…”
Section: Stable Isotope and Fatty Acid Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Powdered muscle tissues were prepared and analyzed for FA profiles followed by the procedure outlined by our previous research (Gong et al, 2018a). Briefly, lipid samples were extracted from approximately 200 mg of dried powders using a mixture of chloroform and methanol.…”
Section: Stable Isotope and Fatty Acid Analysesmentioning
confidence: 99%
“…For example, the SI niche is often based on the range of δ 13 C and δ 15 N values seen in a population (Cucherousset and Villéger, 2015). Although FAs have been used to investigate trophic ecology of ommastrephid squid (e.g., Pethybridge et al, 2012Pethybridge et al, , 2013, and are recognized as efficient tracers for elucidating geographic origins of D. gigas (Gong et al, 2018a), their utility for assessing trophic niche has not yet been determined.…”
Section: Introductionmentioning
confidence: 99%
“…The FA analysis indicates that crustaceans are an important prey for smaller squid, whereas fish constitute a major portion of prey of larger squid [94]. Moreover, on the example of the jumbo squid, Dosidicus gigas, it was shown that an FA analysis can trace the geographic origin of squid individuals [100].…”
Section: Cephalopodamentioning
confidence: 99%
“…Major fatty acids (% of total FAs) in the mantle of squids. Values are mean ± standard deviation (SD)[94,95,[99][100][101].…”
mentioning
confidence: 99%
“…In recent years, there has also been a growing demand to trace the geographic origin of food, whether for nutritional or public health safety reasons. The method of fatty acids composition‐specific isotope analysis was created to achieve the objective of effectively distinguishing food from different geographical sources (Gong, Li, Chen, & Chen, 2018; Ricardo et al., 2015; Zhang et al., 2019).…”
Section: Application Of Ms‐based Lipidomics In Food Sciencementioning
confidence: 99%